1990
DOI: 10.1002/sia.740160190
|View full text |Cite
|
Sign up to set email alerts
|

Defect formation observed by AES in a‐SiO2 films prepared by photochemical vapour deposition

Abstract: Damageless conditions in AES measurement were examined carefully on both thermally oxidized and photochemical vapour deposited amorphous SiO, films as a function of dose rate and total dose. The lower dose rate resulted in the formation of a higher density of oxygendeficient defects under the constant total dose condition. Among the films examined, it was found that Fdoped films prepared by photochemical vapour deposition best resisted electron damage. The results are discussed using the model of defect genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…This result suggests that I contrast decreases faster for lower V irrad . It has been reported that energy dissipation near the surface is larger for lower V irrad [13,14]. It is therefore, suggested that the resistance change occurs near the surface of the NiO film, which is consistent with the V accel -dependence of the SEI contrast shown in Figs.…”
Section: Effect Of Eb Irradiation On C-afm Writing Areasupporting
confidence: 84%
“…This result suggests that I contrast decreases faster for lower V irrad . It has been reported that energy dissipation near the surface is larger for lower V irrad [13,14]. It is therefore, suggested that the resistance change occurs near the surface of the NiO film, which is consistent with the V accel -dependence of the SEI contrast shown in Figs.…”
Section: Effect Of Eb Irradiation On C-afm Writing Areasupporting
confidence: 84%
“…In such a high-spatial resolution AES analysis, the irradiation of primary electrons with the high-current density is required. The irradiation of primary electrons with the high-current density induces the electron-induced damage of a sample surface, such as the reduction of metal oxides [1][2][3][4][5][6][7][8][9][10][11][12]. One of possible mechanisms of the electron-induced damage observed for ionic metal oxides is the Auger decay model investigated in detail by Feibelman and Knotek, in which the electron stimulated desorption of oxygen atoms and ions from the metallic oxide is understood as a result of the Auger decay after the ionization of inner-core level of metal and oxygen atoms [13].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the Si peaks remain somewhat controversial because they have been variously attributed to the growth of Si microcrystals, 2 dangling Si bonds 3,4 and oxygen-deficient centers. 5 The onset for electron beam damage of ion-cleaned, thermally grown oxide has been observed at doses of <1 C cm 2 . 6 Oxygen losses of 20% have been reported after exposures of 80 C cm 2 at dose rates of 13 mA cm 2 .…”
Section: Introductionmentioning
confidence: 99%